Establishment of sheep nasal mucosa explant model and its application in antiviral research - Zheng, Jian; Lin, Jian; Ma, Yichao; Yang, Chengjie; Zhong, Qiu; Li, Yuchen; Yang, Qian (Frontiers in Microbiology, 2023)
The nasal mucosa is the first barrier to pathogen invasion through the respiratory tract. Few studies have focused on nasal resistance to invasion by respiratory pathogens due to the lack of models related to the nasal mucosa. Hence, it is necessary to construct a nasal mucosal model to study host-pathogen interactions. We established a long-term in vitro cultured sheep nasal mucosa explant model (NMEM), which exhibited typical epithelial structure, cilia and epithelial proliferation ability within 11 days. Moreover, to evaluate whether the NMEM was suited for in vitro pathogenic study, we used pseudorabies virus (PRV) and showed that it successfully infected and produced severe lesions in the NMEM, particularly interferon (IFN)-stimulated gene 15 (ISG15) was suppressed. Similarly, we used this NMEM model to screen several antiviral substances, such as probiotics and drugs. Before that, it was found that high abundance of Bacillus was found in the nasal cavity of stocking sheep through sequencing, and 9 strains of Bacillus from stocking sheep were isolated and identified and demonstrated that the NSV2 and NSV3 significantly induced the NMEM production of IFN and expression of ISG15. After nasal spray of NSV2 can also be induced IFNα/β/γ, and ISG15 production. The sheep-derived B. subtilis was pretreated with the sheep NMEM before the PRV infection that NSV2 can significantly inhibited infection by PRV and reduced the viral load. Furthermore, it has similar antiviral effect on cells, and the antiviral effect of NSV2 is attenuated after interfering with ISG15. After NSV2 treatment, the ISGylation level of cells is higher, and there is obvious co-localization between ISG15 and PRV. In conclusion, we established a reliable in vitro culture model of sheep NMEM, and applied in antiviral research.